LW-AFC, A New Formula Derived from Liuwei Dihuang Decoction, Ameliorates Cognitive Deterioration and Modulates Neuroendocrine-Immune System in SAMP8 Mouse - Wang, Jianhui; Zhang, Xiaorui; Cheng, Xiaorui; Cheng, Junping; Liu, Feng; Xu, Yiran; Zeng, Ju; Qiao, Shanyi; Zhou, Wenxia; Zhang, Yongxiang (Current Alzheimer Research, 2017)
Background: Alzheimer’s disease (AD), the most common cause of dementia among older people, could not be prevented, halted, or reversed up till now. A large body of pharmacological study has revealed that Liuwei Dihuang decoction (LW), a classical traditional Chinese medicinal prescription, possesses potential therapeutic effects on AD. LW-AFC is key fractions from LW. Method: Cognition ability was evaluated by behavioral experiments. Using multiplex bead analysis, radioimmunoassay, immunochemiluminometry and ELISA to determine levels of cytokines and hormones. The splenocyte proliferation and peripheral lymphocyte subsets was investigated by 3H-thymidine incorporation and flow cytometric analysis, respectively. Results: This study showed the treatment of LW-AFC slowed the aging process of senescence-accelerated mouse prone 8 strain (SAMP8), a robust model sporadic AD or late-onset/age-related AD. LW-AFC had ameliorative effects on spontaneous locomotor activity, object recognition memory, spatial learning and memory, passive and active avoidance impairment in SAMP8 mice. Administration of LW-AFC restored the imbalance of hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axis, enhanced the proliferation of splenocytes, corrected the disorder of lymphocyte subsets, and regulated the abnormal production of cytokine in SAMP8 mice. Effects of LW-AFC on pharmacodynamics and neuroendocrine immunomodulation network in SAMP8 mice were better than memantine and donepezil. Conclusion: This data indicated LW-AFC may be a promising therapeutic medicine for AD.
Keywords: senescence-accelerated mouse